2020
DOI: 10.3389/fmolb.2020.561456
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Genes in Lung Adenocarcinoma and Establishment of Prognostic Mode

Abstract: Background: The development of human tumors is associated with the abnormal expression of various functional genes, and a massive tumor-based database needs to be deeply mined. Based on a multigene prediction model, access to urgent prognosis of patients has become possible. Materials and Methods: We selected three RNA expression profiles (GSE32863, GSE10072, and GSE43458) from the lung adenocarcinoma (LUAD) database of the Gene Expression Omnibus (GEO) and analyzed the differentially expressed genes (DEGs) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…On the other hand, gene expression profiling holds promise to improve clinical stratification and paves the way for individualized therapy. Zhou et al 14 used a nomogram model to identify six key genes which were combined with various clinical features. The nomogram model led to high consistency for the prediction of 3-and 5-year survival rate (concordance = 0.751) and high accuracy as tested by ROC (AUC = 0.71; AUC = 0.708).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, gene expression profiling holds promise to improve clinical stratification and paves the way for individualized therapy. Zhou et al 14 used a nomogram model to identify six key genes which were combined with various clinical features. The nomogram model led to high consistency for the prediction of 3-and 5-year survival rate (concordance = 0.751) and high accuracy as tested by ROC (AUC = 0.71; AUC = 0.708).…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing GEO datasets of different populations may find different hub genes. A GEO data analysis of the American LUAD population found six hub genes ( VIPR1, FCN3, CA4, CRTAC1, CYP4B1 , and NEDD9 ) related to prognosis ( Jiawei et al, 2020 ). Another study on LUAD populations in Japan and USA found eight hub genes ( GPX3, TCN1, ASPM, PCP4, CAV2, S100P, COL1A1, and SPOK2 ) ( Tu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… 1 Lung adenocarcinoma (LUAD) is the most frequent subtype of lung cancer worldwide, and the 5-year survival rate of LUAD patients is less than 20% and the prognosis is poor. 2 , 3 The classical treatments include surgical resection, postoperative chemotherapy, and postoperative radiotherapy. Since severe damage to the organism caused by radiotherapy and chemotherapy, various targeted drugs aiming at different genetic variants have emerged.…”
Section: Introductionmentioning
confidence: 99%